Systematization of the Wirsung duct and of the Santorini duct (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1976)
The A. studies, by dissecation, the pancreatic duct system in 30 asinines adults (15 males and 15 females); the results obtained show that the Wirsung duct — the main one — results from the union of the collectors of the right and left lobes, and receives, as well (ts its roots, varied number of affluents. A secondary system is composed by the Santorini duct; this one opens, by its central extremity, directly in the Wirsung duct (53.3%), in the duct of the right lobe (23.3%) or in the duct of the left lobe (23.3%).Anastomosis were seen comunicanting, some times (16.7%), diversescollectors of the pancreatic duct system